الإسهامات العلمية والعملية للإمام محمّد بن إبراهيم الفهري البجائي ـ الأصولي ـ (ت612هـ/1215م) - عومري, عقيلة (جامعة الوادي university of eloued, 2023)
ملخص: تهدف هذه الدراسة إلى التعريف بشخصية محمد بن إبراهيم الأصولي خرّيج إحدى الحواضر العلميّة في المغرب الأوسط الذي له إسهامات مختلفة في موطنه وخارجه،حيث قام بأدوار هامّة علميّة بفضل تكوينه المميّز الذي جمع بين العلوم النقلية والعقلية، كما تقلّد مناصب عليا في الدولة الموحديّة،مكّنته من القيام بأحسن الأدوار، العلمية والقضائية والسياسيّة التي نستشف من خلالها المستوى العالي الذي كونته حواضرنا العلمية ،والتكامل المعرفي والمنهجي الذي صبغ هذه الشخصية .Abstract : This study aims to introduce the personality of Muhammad ibn Ibrahim al-Usoli, a graduate of one of the scientific metropolises the Middle Maghreb, who has various contributions in his homeland and abroad, where he played important scientific roles thanks to his distinguished formation that combined both the Transmission and Mental sciences. He also held high posi tions in the Almohads state, which enabled him to perform the best scientific, judicial and political roles through which reflects the high level formed by our scientific metropolises, and the cognitive and methodological integration that characterizes this personality
مقال
Keywords: الأصولي؛ الحواضر؛ الموحديّة؛ النقلية؛العقلية